1991
DOI: 10.1088/0022-3727/24/12/016
|View full text |Cite
|
Sign up to set email alerts
|

Energy efficiency of laser produced C- and T-ion sources

Abstract: The conversion efficiency of laser energy into kinetic ion energy in a laser-produced plasma has been investigated for two quite different targets: graphite and tantalum. The laser energy (intensity) varied from several mJ to 200 ml (I O 9 to 7 x 10" W cm-') which is appropriate to many applications of a lwr produced ion source. The conversion efficiency as a function of the laser energy was directly determined by differential measurements of the charge. kinetic energy and angular emission distribution of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1992
1992
2003
2003

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…In these models, the particle cloud is always treated as a neutral gas. Therefore, coulomb interactions or the coupling of the electrons to the laser field are not considered, although the ions essentially contribute to the total energy in the plasma cloud (Rupp and Rohr 1991).…”
Section: Resultsmentioning
confidence: 99%
“…In these models, the particle cloud is always treated as a neutral gas. Therefore, coulomb interactions or the coupling of the electrons to the laser field are not considered, although the ions essentially contribute to the total energy in the plasma cloud (Rupp and Rohr 1991).…”
Section: Resultsmentioning
confidence: 99%
“…A major argument for taking into account explicitly the role of the ion component in the energy balance during the expansion-at least for plasmas produced by laser intensities above about 10 9 W cm −2 -arises from the fact that in this case the ions always carry the majority of the total energy. Their energy can amount to up to 90% of the total (Rupp and Rohr 1991) even if their relative number is only of the order of 10% and the degree of ionization is as small as about 1% (Gorbonov andKonov 1989, Mann andRohr 1992). Furthermore, one should be aware that ratios of ionic to neutral particles are measured with particle detectors placed at relatively large distances from the target compared with the focal size (typically 0.1-1 m) and that they by no means represent the distributions in the dense focal interaction range.…”
Section: Resultsmentioning
confidence: 99%
“…The total ion current was measured at 308 cm distance from the target using tripleelectrode grid-less collector, where two electrodes were used for ion beam extraction. The extraction voltage on collector U ext = − (12)(13)(14)(15) kV provided the saturation of the measured current signal. The data of measurements on the ion collector and ion analyser were registered using digital oscilloscope LeCroy 9450 and then post-processed by original software.…”
Section: Resultsmentioning
confidence: 99%
“…Careful absolute measurements of the charge, energy and angular emission distribution of the plasma particles (neutral and ion component) as a function of the laser energy were done in works [15][16][17][18] with C, Al, Ti, Ni, Mo and Ta targets for Nd laser pulse duration τ = 5, 14 and 20 ns and laser intensity of P = 4 × 10 9 -7 × 10 10 W cm −2 . It was shown that characteristic ion expansion angle decreases with increase of atomic mass of the target element and charge state of ions.…”
Section: Introductionmentioning
confidence: 99%